The national camp and the concept of a federation during the Second World War - Miszewski, Dariusz (Saeculum Christianum. Pismo Historyczne, 2021)
During the Second World War, the national camp preached the idea of imperialism in Central Europe. Built peacefully, the Polish empire was supposed to protect the independence and security of countries in Central Europe against Germany and the Soviet Union, and thus went by the name of “the Great Poland”. As part of the empire, nation-states were retained. The national camp was opposed to the idea of the federation as promoted by the government-in-exile. The “national camp” saw the idea of federation on the regional, European and global level as obsolete. Post-war international cooperation was based on nation states and their alliances.